2016
DOI: 10.1089/tmj.2015.0071
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of African American Women to Participate in e-Health/m-Health Research

Abstract: Culturally tailored e-health/m-health research using smartphones may be of interest to African American women who are interested in risk reduction and chronic disease self-management. Barriers such as smartphone data plans and privacy will need to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 14 publications
4
68
1
Order By: Relevance
“…The rapid pace access to mobile technologies has resulted in innumerable opportunities for preventive care through mHealth interventions. A 2016 systematic review regarding the use of eHealth/mHealth found that minority groups, such as African Americans, are among the least underrepresented in research using such technologies for health interventions [75]. This is also observed in South American countries, considering that few studies have been conducted using eHealth/mHealth approaches to improve health outcomes associated with chronic diseases [76].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid pace access to mobile technologies has resulted in innumerable opportunities for preventive care through mHealth interventions. A 2016 systematic review regarding the use of eHealth/mHealth found that minority groups, such as African Americans, are among the least underrepresented in research using such technologies for health interventions [75]. This is also observed in South American countries, considering that few studies have been conducted using eHealth/mHealth approaches to improve health outcomes associated with chronic diseases [76].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the findings of other studies that show African American women express greater interest in health issues than African American men (36). Thus, as gatekeepers to the home and a major source of informal health information for the men in their lives, African American women should be considered as primary and secondary targets for mHealth interventions for various health conditions (19). …”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire is described elsewhere (19,20). Questions were asked about sociodemographic characteristics (sex, age, marital status [married or not married], birthplace [in United States or not], education, employment status [employed or not], and home ownership [yes or no]), ownership and use of digital devices, health information–seeking behavior, willingness to participate in mHealth research, weight, and health status.…”
Section: Methodsmentioning
confidence: 99%
“…[20] Many sociocultural factors such as medical racism, low physician referral rates, minimum knowledge about the value of research, economic challenges, and ineffective recruitment strategies have influenced African American women's participation in health research. [21] With African Americans' increasing use of the internet through mobile technology and African American women's frequent use of the Internet to search for health information, there is an opportunity to engage African American women in research through an eHealth intervention for HIV prevention while minimizing some of the common barriers to community-based and clinical interventions. [14,21] To directly address the quandary of little to no awareness of biomedical prevention strategies for HIV prevention among African American women, our study sought to strengthen knowledge of post-exposure prophylaxis and preexposure prophylaxis using eHealth technology in an Internet-based research study.…”
Section: Introductionmentioning
confidence: 99%
“…[21] With African Americans' increasing use of the internet through mobile technology and African American women's frequent use of the Internet to search for health information, there is an opportunity to engage African American women in research through an eHealth intervention for HIV prevention while minimizing some of the common barriers to community-based and clinical interventions. [14,21] To directly address the quandary of little to no awareness of biomedical prevention strategies for HIV prevention among African American women, our study sought to strengthen knowledge of post-exposure prophylaxis and preexposure prophylaxis using eHealth technology in an Internet-based research study. Thus, the purpose of this study was to increase knowledge of the PEP and PrEP for Women eHealth video to increase knowledge of PEP and PrEP using an avatar-led, online, eHealth video in sample of African American women.…”
Section: Introductionmentioning
confidence: 99%